2021
DOI: 10.3389/fgene.2021.720268
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Biological Impacts of Prenatal Nutrition and Selection for Residual Feed Intake on Beef Cattle Using Omics Technologies: A Review

Abstract: Approximately 70% of the cost of beef production is impacted by dietary intake. Maximizing production efficiency of beef cattle requires not only genetic selection to maximize feed efficiency (i.e., residual feed intake (RFI)), but also adequate nutrition throughout all stages of growth and development to maximize efficiency of growth and reproductive capacity, even during gestation. RFI as a measure of feed efficiency in cattle has been recently accepted and used in the beef industry, but the effect of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 125 publications
(213 reference statements)
0
1
0
Order By: Relevance
“…Utilizing RFI as a genetic selection tool can result in offspring that consume less feed at the same level of production. Additionally, since RFI is independent of height, body size, and other traits (Kelly, 2015;Kenny et al, 2018;Foroutan et al, 2021), the selection of animals with low RFI will result in reduced feed intake without affecting body size, skeletal quality, or growth. The study (Culbertson et al, 2015) found no interaction between RFI and sex for growth characteristics and carcass traits, indicating that sex may not significantly impact these phenotypes in beef cattle with high RFI.…”
Section: Pavlodar Farmmentioning
confidence: 99%
“…Utilizing RFI as a genetic selection tool can result in offspring that consume less feed at the same level of production. Additionally, since RFI is independent of height, body size, and other traits (Kelly, 2015;Kenny et al, 2018;Foroutan et al, 2021), the selection of animals with low RFI will result in reduced feed intake without affecting body size, skeletal quality, or growth. The study (Culbertson et al, 2015) found no interaction between RFI and sex for growth characteristics and carcass traits, indicating that sex may not significantly impact these phenotypes in beef cattle with high RFI.…”
Section: Pavlodar Farmmentioning
confidence: 99%